The potential impacts of the implementation of Central Bank Digital Currency (CBDC) towards the Malaysia’s economy - Cheng, Hong Bee; Farm, Tyng Wei; Lim, Xin Ying (2022)
This paper attempts to study the potential impacts of the implementation of central bank digital currency (CBDC) towards Malaysia's economy, we specifically focus on analyzing the potential impact from different perspectives of the implementation of the CBDC in Malaysia to understand whether CBDC can act as a tool to achieve broader public policy outcomes. The research finds that there are four independent variables which are (1) financial stability (FS) - the efficacy of CBDC and its hazards are greatly influenced by the choices made regarding the architecture of CBCD since this novel idea of CBDC may have an impact on the fundamental operations of commercial banks and the role of the central bank. (2) financial inclusion (FI) - CBDC is a financial product and service that everyone can access (3) payment(P) - CBDC is associated with a payment system that enables users to conduct transactions using money that has been digitally issued as legal currency and (4) security & privacy (SP) - The value of CBDC classified material is self-evident, since it may entail national security, vital technologies, or trade secrets. The finding shows the independent variables and dependent variables have a low relationship with the dependent variable which is the willingness of people to use CBDC. But from the view from the significance of the relationship, the independent variables and dependent variables have the significant relationship which all of them less than 0.01 level of significance thus we can reject all the null hypotheses.